Predictive Value of the First Non-Melanoma Skin Cancer: A Retrospective Study - P. M. Garrido; J. Borges-Costa; L. Soares-Almeida; P. Filipe (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Introduction: Patients with previous non-melanoma skin cancer have an increased risk of developing another skin cancer and some studies suggest that the histological type of the incident tumour can predict the one of the subsequently diagnosed. The aim of this study was to assess a correlation between the histological type of the first and the subsequent non-melanoma skin cancer diagnosed in immunocompetent patients and in different settings of immunosuppression. Methods: A retrospective study was conducted on all patients without previous skin cancer, with the diagnosis of two or more non-melanoma skin cancer between January 1st, 2008 and December 31th, 2017. Results: A total of 413 patients were included. Fifty-one individuals (12.4%) were immunosuppressed. There was a significative association between the histological type of the first and the subsequent non-melanoma skin cancer diagnosed both in immunocompetent and in immunosuppressed patients, with a higher probability of developing a tumour of the same histological type (p<0.001). This association was also significative in patients with the diagnosis of a hematologic malignancy. The mean interval between the two diagnoses was 30 months (range 7-111). Forty-three patients (10.4%) presented a subsequent tumour after more than five years of follow-up. Conclusion: The histological type of the incident non-melanoma skin cancer predicted the risk of developing another tumour of the same type. For the first time, we showed this correlation in patients with a hematologic malignancy. High-risk individuals may benefit from a long-lasting follow-up of at least ten years.